Brazil Export Sectors. A Comparative Example with the European Market - Iulia-Monica DUMITRESCU (Revista de Management Comparat International)
This paper is a short outline of the main events that have occurred in Brazil and that have had great economic effects in the evolution of the country during history. The aim of this paper is to bring an economic comparison between the Brazilian economy and some European economies regarding exports. An emphasis is made on the most relevant European countries such as Germany, United Kingdom, Italy and France. Some of the economic sectors of Brazil and the way the GDP is divided between them will also be highlighted. The empirical example outlines the main categories of products that Brazil is exporting to the European countries taken into consideration. A ranking for each of the destination markets has been made based on the value of exports in Euros. The highest 15 values of exports and the 10 lowest export values have been separately outlined for each of the reference countries. The total values of exports for all categories of products for Germany, France, Italy and United Kingdom have also been centralized in order to obtain a more complex comparison. The results have shown interesting findings, many traditional exports of Brazil maintain an important status alongside with modern ones.